Application of Surface-Cracking Process to Improve Impact Toughness of High-Strength BCC Steel at Low Temperatures - Minha Park; Gang Ho Lee; Byoungkoo Kim; Sanghoon Noh; Jong Bae Jeon; Changwoo Lee; Byung Jun Kim (Crystals)
At very low temperatures, typically ductile materials, especially body-centered cubic (BCC) steels, often exhibit an abrupt transition to brittle fracture, significantly limiting their applicability in cryogenic and low-temperature environments. This challenge arises from the inherent properties of BCC steels, where ductility is drastically reduced, leading to unexpected failures under mechanical stress. Despite the advantages of high-strength BCC steels, including cost-effectiveness and mechanical robustness, their susceptibility to brittle fracture restricts their use in demanding low-temperature applications. To address this limitation, we developed an innovative surface-cracking process to enhance the impact toughness of BCC steels. The introduction of controlled surface cracks redistributes stress and energy dissipation mechanisms, improving the toughness of high-strength BCC steels at cryogenic temperatures. Microscopic observations and finite element analyses reveal that these surface cracks not only dissipate crack formation energy but also alter stress triaxiality at crack tips. This causes the stress state to transition toward a plane stress condition, effectively mitigating stress concentrations typically observed in plane strain states. By reducing localized stress severity and promoting uniform energy distribution, the surface cracks encourage failure mechanisms favoring ductile behavior over brittle fracture.